Design of Intelligent Garbage Classification System Based on Internet of Things Technology. Issue 1 (1st February 2022) - Tan, Yanping; Guo, Wei; Yang, Ke; Huang, Jingjing; Yang, Zhengping
Abstract: With the increasingly prominent problem of environmental pollution, it is extremely urgent to carry out garbage classification. This paper designs an intelligent garbage classification system based on Internet of Things technology, The system is mainly composed of relay driving circuit, infrared induction, metal detection and humidity detection modules. Single chip microcomputer and multi-channel sensors are used to collect and process related data to realize metal garbage recovery, dry garbage and wet garbage classification and delivery, and the collected related data are displayed on the display screen through serial communication. The experimental results show that the system has the characteristics of simple structure, stable performance and convenient operation, which provides a feasible solution for the current garbage classification and treatment.